2013
DOI: 10.3945/ajcn.112.050799
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption rate in children after small intestinal transplantation

Abstract: These data indicate a suboptimal intestinal graft absorption capacity with fat malabsorption, which necessitates energy intakes of at least twice the REE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 35 publications
(59 reference statements)
3
34
0
Order By: Relevance
“…Second, in contrast to carbohydrate and protein absorption, there is variable absorption of fat early after transplant, reflected in a relatively large SD seen in the French data 8 . The Pittsburgh series showed that at 3 months, both PN‐dependent and PN‐independent patients had rates of fecal fat excretion (inverse of absorption) of 27.5% ± 4.8% and 26.2% ± 3.9%, respectively, 10 similar to the French data.…”
Section: Studies Of Absorptive Functionmentioning
confidence: 56%
See 2 more Smart Citations
“…Second, in contrast to carbohydrate and protein absorption, there is variable absorption of fat early after transplant, reflected in a relatively large SD seen in the French data 8 . The Pittsburgh series showed that at 3 months, both PN‐dependent and PN‐independent patients had rates of fecal fat excretion (inverse of absorption) of 27.5% ± 4.8% and 26.2% ± 3.9%, respectively, 10 similar to the French data.…”
Section: Studies Of Absorptive Functionmentioning
confidence: 56%
“…One of the most thorough studies on absorptive function of transplanted intestine was recently published by the team from Necker Enfant Malades Hospital, in Paris, France 8 . Detailed 3‐day energy balance studies were performed in a cohort of 24 children (6 with liver‐inclusive grafts, 18 without) at the time of complete cessation of PN with weaning to full enteral nutrition (EN); this occurred at a median of 44 days after transplant.…”
Section: Studies Of Absorptive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth after ITx depends on a myriad of (patho)physiological mechanisms, starting with the intestinal graft function. Ordonez et al demonstrated fat malabsorption in the majority of children during the initial period after weaning PN. Persistent fat malabsorption was observed in nearly all children 2–18 yr after ITx by Lacaille et al In contrast, their cohort demonstrated adequate amino acid and carbohydrate absorption .…”
Section: Discussionmentioning
confidence: 99%
“…Combined intestinal and liver TpX is needed in end stage liver failure, a severe complication in SBS patients on long-term PN due to severe intestinal dysmotility, bacterial translocation, and recurrent sepsis. Patients with intestinal grafts often have a suboptimal absorption capacity which necessitates a significant higher energy and micronutrient intake (Ordonez et al, 2013). However, recently excellent results have been published in cases with U-SBS (see long-term result Chapter 13) (Diamanti et al, 2013).…”
Section: Increasing the Absorptive Surface Areamentioning
confidence: 99%